WILD IN THE CITY: UNAUTHORIZED POSSESSION OF WILD FAUNA IN RESIDENCES OF VALENCIA CITY, BUKIDNON, PHILIPPINES - Khean Harvey Acuevas; Adrian Aturo; Dave Buenavista (SEAMEO BIOTROP, 2026)
ARTICLE HIGHLIGHTS- Covert surveys revealed undocumented wildlife possession within Valencia City residences.- Fifteen species were identified, including three threatened endemic species.- Philippine long-tailed macaque was documented in all study sites.- Human-wildlife interactions may have fueled locals to keep wild animals.- Findings advocate amnesty programs to bolster biodiversity conservation in the urban areas.ABSTRACTThe illegal wildlife trade is a globally recognized industry, and the unauthorized possession of wildlife by locals is a significantly overlooked facet of this field. While significant seizures of poached animals were recorded in the country, many remain undocumented and undetected, specifically in small-scale collections or privately owned wildlife. This study assessed the ownership of wild fauna in five locations in Valencia City, Bukidnon, Philippines. A covert research approach was used to elicit information from the owners, which was done randomly within the months of March to April 2025. A total of 26 owners were interviewed, the majority are male (19; 73%), aged 40 – 45 years old (12; 46%), low-income farmers (17; 65%), and with primary education (16; 62%). The results revealed 63 individuals from 15 species: 8 species of birds, 4 species of mammals, and 3 species of reptiles. Of which, 12 (80%) species are classified as least concern, two (13%) are endangered, and one is undetermined. Birds are the most frequently recorded group (24 individuals), mainly intended for consumption, while Macaca fascicularis philippensis exist across all five barangays because of their behavioral flexibility and presumed human compatibility. Owners’ responses indicate that they keep such animals mainly for recreation or hobby (15; 25%), which reflects the affinity of locals to keep wild animals in the city may have been associated with human-wildlife interactions and humans’ familiarity with native and endemic animals. Therefore, the study recommends strengthening the enforcement of existing national laws and international provisions through community-based conservation models, local wildlife amnesty programs, and partnerships with government and non-government organizations.